Al-‘Ashālāh wa al-Mu’āshirah fī al-Dirāsāt al-‘Islāmīyya - Tulus Mustofa (Al-Jami'ah Research Centre, 1998)
Muslims today are suffered from rational crisis that may lead to the crises of muslim world in many aspects of life. In order to protect and encourage their potentials and dynamism, the muslims have to get out of the illness. One of the ways to save them is by rethinking the methods of studying Islam. This particularly after the decline of muslims in almost all muslim countries as a result of the rise of Western thinking methods introduced by orientalists. Students who devoted themselves in Islamic studies find that there are two contradictive ways of approaching Islam; traditional and modern. The traditionalists try to keep the existing approaches, while the reformists call for reform and even